Designing seryl‐tRNA synthetase for improved serylation of selenocysteine tRNAs. Issue 22 (24th October 2018) - Fu, Xian; Crnković, Ana; Sevostyanova, Anastasia; Söll, Dieter
Abstract : Selenocysteine (Sec) lacks a cognate aminoacyl‐tRNA synthetase. Instead, seryl‐tRNA synthetase (SerRS) produces Ser‐tRNA S ec, which is subsequently converted by selenocysteine synthase to Sec‐tRNA S ec . Escherichia coli SerRS serylates tRNA S ec poorly; this may hinder efficient production of designer selenoproteins in vivo . Guided by structural modelling and selection for chloramphenicol acetyltransferase activity, we evolved three SerRS variants capable of improved Ser‐tRNA S ec synthesis. They display 10‐, 8‐, and 4‐fold increased k cat / K M values compared to wild‐type SerRS using synthetic tRNA S ec species as substrates. The enzyme variants also facilitate in vivo read‐through of a UAG codon in the position of the critical serine146 of chloramphenicol acetyltransferase. These results indicate that the naturally evolved SerRS is capable of further evolution for increased recognition of a specific tRNA isoacceptor. Abstract :